Bonggang Bonggang Bongbong: Ang Rehabilitasyong Pulitikal ng mga Marcos - Mendoza Jr., Amado; Llanes, Ferdinand C.; Eusebio, Gerardo; Hernandez, Butch (Kasarinlan: Philippine Journal of Third World Studies; Vol 27, No 1-2-Vol 28, No 1-2 (2012-2013): Marcos Pa Rin! The Legacy and the Curse of the Marcos Regime, 2017)
Proceedings of the third "Marcos Pa Rin!" forum.